Antarctic krill-derived peptides with consecutive Glu residues enhanced iron binding, solubility, and absorption. Issue 18 (3rd August 2021) - Hu, Shengjie; Lin, Songyi; Wang, Di; Zhang, Shuyue; Sun, Na
Abstract : Exploration of the iron-binding properties, digestive stability, and effectiveness on enhancing iron solubility and absorption of Antarctic Krill-derived peptides with consecutive Glu residues. Abstract : Three peptides containing three glutamic acid (Glu) residues at different positions derived from Antarctic krill were obtained to investigate their iron-binding properties, digestive stability, and effectiveness on enhancing iron solubility and absorption. Results indicated that Fe 2+ bound to the carbonyl, carboxyl, or hydroxyl groups of DELEDSLER, EEEFDATR, and DTDSEEEIR at stoichiometric ratios of 0.453, 0.466, and 0.490, respectively. DTDSEEEIR with three consecutive Glu in the middle of the sequence possessed higher iron-binding ability and iron release potential than EEEFDATR with three consecutive Glu in the N-terminal, and DELEDSLER with three discontinuous Glu showed the lowest values. Although EEEFDATR showed remarkably lower digestion stability than DTDSEEEIR, the effect of EEEFDATR–iron on iron solubility and absorption was comparable to that of DTDSEEEIR–iron, but better than that of DELEDSLER–iron and FeSO4 . Thus, peptides with consecutive Glu have the potential as an effective iron carrier to improve iron absorption.